Lagged Identification Rate (LIR) of humpback whales in the Kitimat Fjord System. - Janie Wray (457395); Eric Keen (11014169); Éadin N. O’Mahony (11014172) (2021)
Left : Grey dots represent the LIR calculated for each time lag ( τ , in days) tested. Black line is the running mean of LIR (window = 10 days, first point forced to the τ = 1). Blue line and shaded area represent the median and 95% confidence interval (2.5% and 97.5% quantiles), respectively, of the permutation tests (n = 100). Lags at which the running mean rises above the shaded area indicate significant patterns in residency behavior. Right : Best-fitting SOCPROG model of LIR (note log scale). Points with standard errors (n = 100 bootstraps) are lag-pooled calculations of the LIR, computed at τ = 2 0–8 . Orange line represents the best-fitting model (see S6 Table in S1 File ).